2022
DOI: 10.1186/s13006-022-00465-w
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for breastfeeding during Coronavirus Disease 2019 (COVID-19) pandemic

Abstract: Background Coronavirus Disease 2019 (COVID-19) has spread worldwide. The safety of breastfeeding of SARS-CoV-2-positive women has not yet reached a consensus among the scientific community, healthcare providers, experts in lactation care, health organizations and governments. This study was conducted to summarize the latest evidence about the safety of breastfeeding among suspected/confirmed infected mothers and to summarize the recommendations on breastfeeding during COVID-19 from different or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Precautions for direct breastfeeding put forward by the above organizations included washing hands before touching the infant, wearing a medical mask during any contact with the infant, and routinely cleaning and disinfecting surfaces that mothers had touched. Precautions for expressing breast milk included wearing a mask during expression, washing hands before touching any pumps/bottle parts and expressing breast milk, following recommendations for proper pump cleaning after each use, and feeding expressed milk to the infant by a healthy caregiver who was not at risk for COVID-19, if possible [26]. This is the first study to highlight the lack of healthcare information and support in breastfeeding women with SARS-CoV-2 infection, and our results are in line with previously published data on non-infected women during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Precautions for direct breastfeeding put forward by the above organizations included washing hands before touching the infant, wearing a medical mask during any contact with the infant, and routinely cleaning and disinfecting surfaces that mothers had touched. Precautions for expressing breast milk included wearing a mask during expression, washing hands before touching any pumps/bottle parts and expressing breast milk, following recommendations for proper pump cleaning after each use, and feeding expressed milk to the infant by a healthy caregiver who was not at risk for COVID-19, if possible [26]. This is the first study to highlight the lack of healthcare information and support in breastfeeding women with SARS-CoV-2 infection, and our results are in line with previously published data on non-infected women during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, antibodies of SARS-CoV-2 may be transferred from infected or healthy vaccinated lactating mothers to newborns through breastfeeding, with a potential protective effect. 79 Long-COVID-19 syndrome: differences between men and women As above mentioned, the SARS-CoV-2 pandemic has clearly demonstrated that sex and gender-related factors play role in COVID-19 vulnerability, both in the acute phase and in the postinfection period. Therefore, it is imperative to collect sex-disaggregated data in order to better understand the differences in the pathophysiologic mechanisms of COVID-19 and to implement effective treatment and prevention.…”
Section: Pregnancy Outcomes and Covid-19 Infectionmentioning
confidence: 94%
“…Conversely, antibodies of SARS-CoV-2 may be transferred from infected or healthy vaccinated lactating mothers to newborns through breastfeeding, with a potential protective effect. 79 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard recommendations during the COVID-19 epidemic suggest that who test positive mothers can feed their babies with infection control and prevention measure. [78][79][80][81][82][83] If the mother-baby dyad test positive for COVID-19, breast feeding is not contraindicated. 84 If both the mother and her newborn are hospitalized and separated from each other, expressed breast milk can be given.…”
Section: Importance Of Human Milk Bank In Covid-19 Pandemicmentioning
confidence: 99%